Calcified pancreatoduodenal artery aneurysm with filiform celiac stenosis: Follow up for ~6 years (70 months) with no intervention - Zhanar Kozhakhmetova; Ulugbek Alimov; Galymzhan Kuatbay (National Scientific Medical Center, 2022)
A 72-year-old male patient was investigated with abdominal ultrasound (US) imaging before the coronary artery bypass graft surgery (CABG). The incidental finding on ultrasound was an aneurysm of the superior mesenteric artery branch. Consequent CT angiography confirmed aneurysm of the inferior pancreaticoduodenal artery (PDAA, size = 25,5x31,0x28,5mm) with filiform celiac artery stenosis. According to the European Guideline asymptomatic >25mm sized PDAA are treated with an urgent repair. However, the discrepancy between PDAA size and risk of rupture and individual parameters of the patient led the multifunctional team to assign regular follow-ups with US imaging. This case report describes rare pathology, which has been followed up for the last ~6 years (70 months) annually with no intervention, and discusses complexities in making decisions in the management of PDAA with celiac artery stenosis.